الاحتياجات التّدريبية لدى معلّمي المرحلة الابتدائيّة الطور الثّاني في مجال بناء الاختبارات التّحصيلية الموضوعيّة - ساعد, صباح (Sciences de l'Homme et de la Société, 2013)
تعدّ الاختبارات التّحصيليّة الموضوعيّة من بين أهم أدوات التّقويم التّربوي، حيث يتمّ بناء على نتائجها اتخاذ العديد من القرارات المتعلّقة بمصير الملايين من التّلاميذ. ولقد أثبتت العديد من الدّراسات ضعف كفاية المعلّمين في مجال بناء الاختبارات التّحصيليّة الموضوعيّة. لذلك تعدّ قضيّة تدريب المعلّمين لتنمية كفايتهم في هذا المجال، من الأمور الأساسيّة والواجب أخذها بعين الاعتبار. وجاءت هذه الدّراسة من أجل الكشف عن الاحتياجات التّدريبيّة لدى معلّمي المرحلة الابتدائية في مجال بناء الاختبارات التحصيليّة الموضوعيّة.   The objective achievement tests, are among the most important tools for educational assessment, as it is on the basis of their results that many decisions are made concerning the fate of millions of students; and many studies have confirmed the weakness of the adequacy of teachers in constructing objective achievement tests. So, the issue of teachers training for the development of their adequacy in this area is essential and must be taken into account. The present study came to detect training needs of primary school teachers in the field of constructing objective achievement tests.